2023
DOI: 10.3390/s23031257
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm for Online Stochastic Error Modeling of Inertial Sensors in Urban Cities

Abstract: Regardless of whether the global navigation satellite system (GNSS)/inertial navigation system (INS) is integrated or the INS operates independently during GNSS outages, the stochastic error of the inertial sensor has an important impact on the navigation performance. The structure of stochastic error in low-cost inertial sensors is quite complex; therefore, it is difficult to identify and separate errors in the spectral domain using classical stochastic error methods such as the Allan variance (AV) method and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…They conducted experiments to validate the method's effectiveness for testing the bandwidth of fibre-optic gyroscopes, and the experimental outcomes demonstrated that the compensated signal accurately determined the fibre-optic gyroscope's bandwidth. Zhao et al proposed an online random error calibration algorithm that combines static detection with an adaptive threshold and further develops an autonomous random error model by constructing a complete random error model and determining its ranking criteria [11]. Narasimhappa et al [12] introduces a random IMU error model in Sage Husa adaptive robust Kalman filters.…”
Section: Introductionmentioning
confidence: 99%
“…They conducted experiments to validate the method's effectiveness for testing the bandwidth of fibre-optic gyroscopes, and the experimental outcomes demonstrated that the compensated signal accurately determined the fibre-optic gyroscope's bandwidth. Zhao et al proposed an online random error calibration algorithm that combines static detection with an adaptive threshold and further develops an autonomous random error model by constructing a complete random error model and determining its ranking criteria [11]. Narasimhappa et al [12] introduces a random IMU error model in Sage Husa adaptive robust Kalman filters.…”
Section: Introductionmentioning
confidence: 99%
“…MEMS gyroscope plays an important role in industrial equipment, inertial navigation systems, and other fields because of their small size and low power consumption [1]. However, the complexity of MEMS gyroscope processing and the variability of the operating environment result in a lot of random noise in the gyroscope's output signal, which seriously affects the performance of MEMS gyroscopes [2,3]. Therefore, to improve the accuracy of the MEMS gyroscope, it is necessary to comprehensively analyze the random noise characteristics of the MEMS gyroscope and assess its performance.…”
Section: Introductionmentioning
confidence: 99%